Bleak House: Analogy and Intrigue as Narrative Techniques - Neupane, Shree Prasad (New Journey, 2025)
This study entitled, “Bleak House: Analogy and Intrigue as Narrative technique’’ deals with the issue of the judicial evils presented in England during the 19th century. The main source of justice is the court that should provide equal rights to the citizens and it should protect the basic rights of the citizens. The British Chancery Court is analogically presented in the novel. Fog analogically represents the court. Fog has covered everything like boats, rivers, green meadows and everything else. As in fog, nothing can be seen clearly about the Chancery Court. Several counsels and solicitors looked through the paper work of the court case called Jarndyce and Jarndyce which has gone for generations. But no one knows the reality about the case. So, the main problem of this study is to clarify how British Chancery Court has been polluted and the citizens are deprived of justice in British society. The main objective of the study is to identify the social evils created by the misuse of Chancery Court in Britain. The present study is qualitative in its nature and the use of figures of speech specially analogy and intrigue are studied in the novel. The events, setting and even the characters and their roles are studied, analyzed and interpreted the role of the court through the use of figure of speech. It is found that the nineteenth century British society was totally corrupted. The main source of justice that is the court was limited only in the hands of some limited people. They utilized the court only for their favor.